2015
DOI: 10.1371/journal.pone.0144669
|View full text |Cite
|
Sign up to set email alerts
|

Scaling Chromosomes for an Evolutionary Karyotype: A Chromosomal Tradeoff between Size and Number across Woody Species

Abstract: This study aims to examine the expected scaling relationships between chromosome size and number across woody species and to clarify the importance of the scaling for the maintenance of chromosome diversity by analyzing the scaling at the inter- & intra-chromosomal level. To achieve for the goals, chromosome trait data were extracted for 191 woody species (including 56 evergreen species and 135 deciduous species) from the available literature. Cross-species analyses revealed a tradeoff among chromosomes betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…Karyotypes can yield valuable information regarding the highest level of structural and functional organization of chromosomes that are the main carriers of genetic material within the nuclei of each eukaryotic cell [13]. The more closely related species are, the more similar karyotypes they share [14].…”
Section: Introductionmentioning
confidence: 99%
“…Karyotypes can yield valuable information regarding the highest level of structural and functional organization of chromosomes that are the main carriers of genetic material within the nuclei of each eukaryotic cell [13]. The more closely related species are, the more similar karyotypes they share [14].…”
Section: Introductionmentioning
confidence: 99%
“…This indicated that the TCN may have evolved from more to less in woody plants because deciduous species had more m-chromosomes while evergreens had more total chromosomes number in their nuclei. The increase in TCN will trigger an increase in m-chromosomes at a 1.5-fold faster rate [13]. Increasing the number of m-chromosomes preserves karyotype symmetry which opposes the minimum interaction theory mentioned above.…”
Section: Chromosome Number Evolution (Change)mentioning
confidence: 91%
“…It has been considered as an essential taxonomic and evolutionary criterion of living species [13][14][15][16]. The minimum interaction hypothesis of karyotype introduced by Imai et al [17] suggested that the karyotype usually tends to increase the number of acrocentric and reduce the formation of metacentric chromosomes (m-chromosomes) [17,18].…”
Section: Chromosome Number Evolution (Change)mentioning
confidence: 99%
“…Each species has a characteristic chromosome complement, the karyotype (Jiang, 2019), which represents the highest level of structural and functional organization of genome (Weiss-Schneeweiss and Schneeweiss, 2013; Liang and Chen, 2015). Karyotypic features have greatly facilitated taxonomic and systematic studies, and they have also provided important insight into genome size estimations as well as genome structure and organization at the chromosomal level in numerous plant species (Chèvre et al, 2018), including radish (Raphanus sativus L.) (He et al, 2015), Coix lacryma-jobi L. and Coix aquatica Roxb.…”
Section: Introductionmentioning
confidence: 99%
“…(Deng et al, 2019a). Elucidating chromosome constitution and the karyotype including the number, absolute and relative size, symmetry, and centromere position of the chromosome complement in nucleus cell of individual eukaryotic species, is a fundamental question in plant biology (Liang and Chen, 2015;Jiang, 2019). Nevertheless, up to now, the chromosomal characterization of CC rootstock remains unexplored, partly because of its inherent small size and morphological similarity of mitotic chromosomes as well as the paucity of accessible chromosome landmarks in the Aurantioideae subfamily (Krug, 1943;Silva et al, 2015).…”
Section: Introductionmentioning
confidence: 99%